1994
DOI: 10.1002/polb.1994.090321110
|View full text |Cite
|
Sign up to set email alerts
|

Properties of polystyrene‐poly(methylmethacrylate) random and diblock copolymers in dilute and semidilute solutions

Abstract: Solution properties for random and diblock copolymers of polystyrene (PS) and poly(methyl methacrylate) (PMMA) have been measured by dynamic and total intensity light scattering in solvents of differing quality. The results are compared with the corresponding properties for PS and PMMA homopolymers of similar molecular weight, in order to determine if interactions between unlike monomers are significant. The hydrodynamic radius (Rh) and diffusion second virial coefficient (kd) for the random copolymer are foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Some experimental studies have been reported on dilute, semi-dilute, and concentrated solutions of random and block copolymers. [107,108] …”
Section: Coil-globule Transition Of Copolymersmentioning
confidence: 98%
“…Some experimental studies have been reported on dilute, semi-dilute, and concentrated solutions of random and block copolymers. [107,108] …”
Section: Coil-globule Transition Of Copolymersmentioning
confidence: 98%
“…[6][7][8][9] To a similar degree as molecular weight and chemical composition, the segmentation of copolymers was shown to have a major impact on the physical properties of the resulting materials, including their stability, solvation or self-assembly behaviour. [10][11][12][13] For example, polymer sequence was demonstrated to affect the glass transition temperature of copolymers of ethylene glycol methyl ether acrylate (EGMEA) and tert-butyl acrylate (tBA). 14 In other example, segmentation was also shown to have a dramatic influence on the interaction of copolymers with lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation functions were obtained on either of two instruments, as previously described [9,10]; each employs an Ar+ laser operating at 488 nm. Scattering angles ranged from 30 to 135 degrees.…”
Section: Apparatusmentioning
confidence: 99%